Scent of COVID-19: Whole-Genome Sequencing Analysis Reveals the Role of ACE2, IFI44, and NDUFAF4 in Long-Lasting Olfactory Dysfunction - Beatrice Spedicati; Alessandro Pecori; Maria Pina Concas; Aurora Santin; Romina Ruberto; Giuseppe Giovanni Nardone; Andrea D’Alessandro; Giancarlo Tirelli; Paolo Boscolo-Rizzo; Giorgia Girotto (Life)
COVID-19-related persistent olfactory dysfunction (OD) presents remarkable interindividual differences, and little is known about the host genetic factors that are involved in its etiopathogenesis. The goal of this study was to explore the genetic factors underpinning COVID-19-related OD through the analysis of Whole Genome Sequencing data of 153 affected subjects, focusing on genes involved in antiviral response regulation. An innovative approach was developed, namely the assessment of the association between a “gene score”, defined as the ratio of the number of homozygous alternative variants within the gene to its length, and participants’ olfactory function. The analysis highlighted how an increased gene score in the ACE2 gene is associated with a worse olfactory performance, while an increased gene score in the IFI44 and NDUFAF4 genes is associated with a better olfactory function. Considering the physiological role of the proteins encoded by these genes, it can be hypothesized that a reduced expression of ACE2 may be associated with a protracted and severe inflammatory response in the olfactory epithelium, thus worsening patients’ smell abilities. Conversely, an increased gene score in IFI44 and NDUFAF4 might be associated with a decreased inflammatory response, thus correlating with a better olfactory performance. Overall, this study identified new host genetic factors that may play a pivotal role in determining COVID-19-related OD heterogeneity, possibly enabling more personalized and effective clinical management for affected individuals.